Professional Responsibility as a Tool for Developing the Managerial Competence of Leaders in General Education Institutions - Khurramov Anvar Vafokulovich (Zien Journals, 2026)
This article examines, on a scientific basis, the role of professional responsibility in the formation and development of managerial competence of leaders in general education institutions. It is determined that the level of a leader’s professional responsibility is closely associated with the effectiveness of managerial activity, the accuracy of decision-making, and the ability to manage and coordinate the work of the pedagogical staff. The article analyzes the concept of professional responsibility, its structural components, and its influence on leadership activity. Based on the analysis, scientific and practical recommendations are developed to improve the management process in general education institutions
Keywords: professional responsibility; educational leader; managerial competence